Automatic Control of Irrigation and Increased Fertilization Frequency to Improve Lemon Production Under Dry Conditions - Abdelraouf Ramadan Eid; Baher M. A. Amer; Basem M. M. Bakr; Mohamed A. El-Shawadfy; Mamdouh A. A. Abdou; Waleed M. E. Fekry; Mohamed Farig; Khaled A. Metwally; Hassan H. H. Tarabye (Horticulturae, 2025)
In order to sustain food production under conditions of limited water and in arid regions using the least amount of irrigation water possible, two experiments were conducted during the years 2021 and 2022 in the Nubaria region, Egypt. The performance of an automated drip irrigation control system was evaluated as a potentially efficient and sustainable alternative to manual irrigation to increase the fertilization frequency (N P K) of lemon trees. This study underlines the importance of automatically applying and controlling the addition of irrigation water as a sustainable alternative to manual irrigation, while increasing the number of mineral fertilization times under sandy soil conditions to the largest possible number (12 times during the growing season of lemon trees) instead of three times. The application of automatic irrigation reduced the water stress on the roots of the lemon trees, in addition to increasing the efficiency of the addition. The latter led to the creation of a healthy environment in the area where the roots spread and increased the rate of absorption of irrigation water loaded with the necessary major elements, thus increasing the canopy volume of the lemon trees. This, in turn, led to an improvement in the efficiency of the photosynthesis process, resulting in an increase in the productivity, water productivity, and quality characteristics of lemon in sandy soil in dry areas. Increasing the number of times of mineral fertilization to 12 during the growing season led to a long-term increase in the concentrations of those minerals within the area of root spread, avoiding losing them by deep percolation, as occurs fertilization is carried out only three times per season. The highest values of the productivity and irrigation water saving were 47.6% and 47.4%, respectively, during the first season and 48.7% and 48.8%, respectively, during the second season. The highest values of water productivity and lemon fruit quality were also achieved under the same conditions. Therefore, this study recommends the automatic control of irrigation schedules, in addition to increasing the frequency of fertilization times, not only in lemon plantations, but also with most horticultural fruit trees grown in dry sandy lands.